KOMUNIKASI KELOMPOK DAN ORGANISASI - Illa Rohillah; Ira Septi Sulistiana (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to understand the role of effective communication in supporting the dynamics of group and organizational work. Using a qualitative descriptive approach, this study explores the direct experiences of group and organizational members in various sectors, such as education, private sector, and social communities. Data were collected through in-depth interviews, participant observation, and analysis of organizational documents. The results of the study indicate that effective communication contributes significantly to the achievement of group and organizational goals. In the context of a group, open and participatory communication strengthens a sense of togetherness, increases motivation, and encourages innovation. At the organizational level, structured and transparent communication helps maintain vision alignment, strengthens work culture, and supports better decision-making processes. This study also identified various communication barriers, such as differences in perception, rigid hierarchies, and limited digital communication skills. Therefore, strategic efforts are needed to build an inclusive communication culture, provide communication training, and utilize communication technology optimally.